(3GdOQI GdjJjeIs - (3CMeO Hf GdMSjf Hf Ydjs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdEfSGf YfhGf Ybd GdEfSGf hHYO aEfi deG QCjJ JZGjQ eYGfiGdCNdGb Ydi JHGjf eHGfi GdGZQGb GdHGH GdChd ai GdSdWGfjGJ s
(3BNQgG (B:s
(3aYdjc HgPg GdCNdGb Cf CWbJ hdf JWjb hdcf CNP Gdbdjd NjQ ef JQc GdLejY hHGddg GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HBNQg aGFOIs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI jMi HGTG GdLdjdi GdehUd (B(416) s
Keywords: (3GdSjGSI hGdGLJeGYs